2014
DOI: 10.1016/j.vaccine.2014.01.091
|View full text |Cite
|
Sign up to set email alerts
|

Educational interventions to increase HPV vaccination acceptance: A systematic review

Abstract: Background The Human papillomavirus (HPV) vaccine has been available for protection against HPV-associated cervical cancer and genital warts since 2006. Nonetheless, uptake has varied among countries and populations within countries. Studies have found that individuals’ knowledge and attitudes toward the vaccine are associated with immunization uptake. The purpose of the current review is to summarize and evaluate the evidence for educational interventions to increase HPV vaccination acceptance. Methods We s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
253
1
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 257 publications
(265 citation statements)
references
References 58 publications
(208 reference statements)
7
253
1
4
Order By: Relevance
“…While educational interventions are helpful to increase acceptance in adolescent and young adult samples, education interventions among parental samples of adolescents are mixed. 3 Hence, our messages may not have effectively impacted intention and vaccine receipt because parents had a more significant concern that needed to be addressed. Future research is needed to assess whether message sidedness interventions targeting multiple health beliefs or tailored specifically to the meet the parents' health belief concerns regarding HPV vaccination increase intentions and uptake.…”
Section: 2mentioning
confidence: 99%
See 2 more Smart Citations
“…While educational interventions are helpful to increase acceptance in adolescent and young adult samples, education interventions among parental samples of adolescents are mixed. 3 Hence, our messages may not have effectively impacted intention and vaccine receipt because parents had a more significant concern that needed to be addressed. Future research is needed to assess whether message sidedness interventions targeting multiple health beliefs or tailored specifically to the meet the parents' health belief concerns regarding HPV vaccination increase intentions and uptake.…”
Section: 2mentioning
confidence: 99%
“…2 Interventions that have attempted to increase HPV immunization have had mixed results and many have necessarily used vaccine intent, rather than vaccine receipt, as the primary outcome. 3 In addition, most interventions have targeted vaccination intent for girls and young women using a variety of samples, including adolescents, college-enrolled women and parents of the college aged women. 3 Across all groups, low rates of HPV vaccine initiation and series completion have been widely reported in the context of traditional settings, such as physician offices, where logistical and financial barriers may present obstacles to immunization.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Fu et al reviewed 33 articles describing educational interventions and concluded that no specific strategy merited recommendation. 20 However, the included studies did not consistently report postintervention vaccination rates, complicating interpretation of intervention success. Niccolai et al reviewed 14 community and clinic interventions and found several successes.…”
mentioning
confidence: 99%
“…Various educational strategies in healthcare practice or community settings have shown to be effective in improving parental HPV vaccine knowledge and uptake. [25,26] Although educating parents plays a key role in their decision-making process, the impact of the parentprovider relationship and strength of provider recommendation on HPV vaccination uptake or intent has not been fully examined. [12] …”
Section: Introductionmentioning
confidence: 99%